Rising China Global Challenges and Opportunities - Golley, Jane (ANU Press, 2011)
Where the last three decades of the 20th century witnessed a China rising on to the global economic stage, the first three decades of the 21st century are almost certain to bring with them the completion of that rise, not only in economic, but also political and geopolitical terms. China's integration into the global economy has brought one-fifth of the global population into the world trading system, which has increased global market potential and integration to an unprecedented level. The increased scale and depth of international specialisation propelled by an enlarged world market has offered new opportunities to boost world production, trade and consumption; with the potential for increasing the welfare of all the countries involved. However, China's integration into the global economy has forced a worldwide reallocation of economic activities. This has increased various kinds of friction in China's trading and political relations with others, as well as generating several globally significant externalities. Finding ways to accommodate China's rise in a way that ensures the future stability and prosperity of the world economy and polity is probably the most important task facing the world community in the first half of the 21st century. The book delves into these issues to reflect upon the wide range of opportunities and challenges that have emerged in the context of a rising China.